(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The necessity of using modern approaches to managing education as an integral element of the economy, which is the driver of professional growth and changes in society, is substantiated. The features and key aspects of the formation of the institutionalization of education management in a separate university with the aim of ensuring the quality of modern education and the effectiveness of its management are considered. An in-depth analysis of the quality of educational services; a conceptualized comparison of education level indices, ratings of national education systems and their effectiveness in countries of the world. This article discusses about modern approaches to the organization of the educational process and their peculiarities